Urban Forestry and Arboriculture in Malaysia An Interdisciplinary Research Perspective - Maruthaveeran, Sreetheran; Chen, Wendy Y.; Morgenroth, Justin (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book represents the latest research on urban forestry in a Malaysian context. It demonstrates that urban forestry is concerned not only with environmental enhancement, but also other aspects, such as recreation, health and well-being, and government policies. This edited collection provides a comprehensive overview of urban forestry studies from various researchers in Malaysia, and includes rich historical perspectives of urban forestry in the country. It also tackles related issues in policy. The greening of urban Malaysia in the 1970s focused primarily on beautification and was primarily the province of horticulturists, landscapers, nursery workers, town planners, and architects, with negligible inputs from foresters, particularly urban foresters. Perhaps for that reason, the term "landscaping" has been used more widely than "urban forestry" by government and private institutions, politicians, stakeholders, academicians, and the public. Nevertheless, the authors show that the concept of urban forestry is not new for developing countries such as Malaysia, where urbanization is increasing at a rapid rate. The book unpacks this demographic shift from a predominantly rural to a principally urban society. As the only unified body of work on urban forestry and arboricultural studies in Malaysia, this volume presents an important interdisciplinary reference for students, researchers, and scholars in physical geography, forestry and urban forestry, arboriculture and landscape architecture, both in Malaysia, and in other developing urbanizing countries, particularly in Southeast Asia. It is also an important resource for those working in environmental policy and practice, excavating the vital connection between the environment and well-being.
Historical Perspective of Urban Forestry and Arboriculture in Malaysia -- Status and Future of Urban Forestry in Sabah, Malaysia -- Tree Preservation Order of Act 172 -- Effects of Tree Shading in Modifying Tropical Microclimate and Urban Heat Island Effect -- Influence of Roadside Trees and Road Orientation on Outdoor Thermal Environment: Case Study in Kuala Lumpur, Malaysia -- Effect of Paclobutrazol and Potassium Nitrate in Improving the Flowering Performance of Xanthostemon chrysanthu -- Urban Trees as a Nature Based Solutions for Carbon Sequestration in Malaysia -- The Effects of Creeping Plants on The Acoustical Performance of Green Porous Concrete Noise Barriers -- Soil and water bioengineering technique for ecological restoration and mitigation of natural hazards -- Insect Pests of Malaysian Urban Trees -- The Malaysian Perspective: Urban Forestry for Human Health and Wellbeing in the Tropics -- Urban Green Space, Green Exercise and Health Outcomes: Evidence from Kuala Lumpur, Malaysia -- Urban Soil Environment in Malaysia.
Keywords: Environmental sciences-Social aspects; Sociology, Urban; Physical geography; Environmental health; Forestry; Well-being.; Environmental Social Sciences; Urban Sociology; Physical Geography; Environmental Health; Forestry; Well-Being.